Sosialisasi dan Pembuatan Spray Anti-Nyamuk Alami dari Serai dan Jeruk sebagai Upaya Pencegahan DBD - Cindy Farera Claudia; Silvia Nur Safitri; Farrel Sabilillah Putra Achmad; Ahmad Fatih Al Ghifari; Danisa Putri Hapsari; Marshyanda Putri Nurhidayah; Fraziz Wicaksono Abdul Salam; Byar Sanjaya Sri Krisna; Tukiman Tukiman (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This community service program aimed to socialize and produce a natural mosquito-repellent spray made from lemongrass and oranges as an effort to prevent Dengue Hemorrhagic Fever (DHF). Through this program, the community was provided with knowledge about the benefits and methods of making environmentally friendly and safe natural sprays. The methods used involved socialization, spray-making demonstrations, and testing its effectiveness against Aedes aegypti mosquitoes. The results showed that the spray produced was able to repel up to 90% of mosquitoes at the highest concentration (10%). This program not only increased public awareness of DHF prevention but also empowered them to create products beneficial for health and the environment.